DEVELOPMENT OF BOOKLET BASED SCIENCE LEARNING MEDIA FOR JUNIOR HIGH SCHOOL - Cips Nur Aini; Mohammad Wildan Habibi (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This research is motivated by the low interest in student learning in science subjects, especially class VII Biology material which assumes that Biology material is identical to a lot of writing in books and contains a lot of memorization, educators have not used school facilities to develop learning media and minimal teaching materials are only in the form of worksheets. Students are not interested in learning science. The school is a pesantrenbased school, where students only get information from the LKS and the material delivered by the teacher. One of the interesting learning media is the booklet- based science learning media. This study aims to determine the validity of booklet media and student responses to booklet media. The type of research used is Research and Development which refers to the 4D development model (Define, Design, Development, and Dissemination) from S. Thiangarajan (1974) which has been modified into 3D. The results showed that the results of the material expert validation obtained a percentage of 92%; media experts obtained a percentage of 97.77%; by science teachers obtained a percentage of 100%. Small-scale trials obtained a percentage of 91.06% and large-scale trials obtained a percentage of 92.72%. This it can be concluded that the booklet- based science learning media on the material of the interaction of living things with their environment is valid to be used as a media for learning science biology in class VII MTs / SMP